Is pulmonary tuberculosis in pregnant women a problem in Ghana? Observations and lessons from the National Tuberculosis Prevalence Project - Awua‑Boateng, Nana Yaa; Mohammed, Aliyu; Aglanu, Leslie Mawuli; Acheampong, Godfred; Amuasi,J. H.; Bonsu,F.A.; Phillips, Richard Odame; Owusu-Dabo, Ellis (Wolters Kluwer - Medknow, 2020)
An article published by Wolters Kluwer - Medknow